Preliminary Insulated Pipeline with Self-Compensating System of Double Pipes - S. I. Abrazhevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a possibility to reduce expenses while laying power-and-heat supply pipeline by using preliminary insulated self-compensating pipes. The problem of automated design of power-and-heat supply pipeline is formulated in the paper.